Performance Evaluation of Palm-Olein TMP Ester Containing Hexagonal Boron Nitride and an Oil Miscible Ionic Liquid as Bio-Based Metalworking Fluids / Amiril Sahab Abdul Sani ...[et al.] - Abdul Sani, Amiril Sahab; Abd Rahim, Erween; Talib, Norfazillah; Kamdani, Kamaruddin; Rahim, Mohammad Zulafif (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Bio-based lubricants from vegetable oils are seen as a great potential alternative to the ever declining petroleum oil sources. Vegetable oils are highly biodegradable and non-toxic, pose good lubricating properties and do not require high production costs. Palm oils as the main renewable oil sources in Southeast Asia are being widely used as cooking oils. Researches have been conducted to expand their potential usage as lubricants for manufacturing applications. In this study, a chemically modified palm olein trimethylolpropane (TMP) ester (MRPO) containing various additives has been tested for their tribological characteristics. Two types of additives; hexagonal boron nitride (hBN) nanoparticles as solid lubricants and phosphonium-based ionic liquid (PIL) as an oil-miscible liquid additive were added into the MRPO to enhance its physical and tribological properties. Four ball wear tests were performed on steel/steel contacts lubricated with each of the lubricant samples. The experimental results presented improved physical properties as well as good antiwear and antifriction performances of the lubricant mixtures compared to the base oil. A minute quantity of PIL (1 wt. %) and hBN nanoparticles (0.05 wt. %) are found to increase the tribological performance of the MRPO, as well as when they are mixed together as lubricant additives into the base oil. The tribological improvements posed by the MRPO+PIL1% revealed better than or comparable results to the conventional synthetic ester and therefore is seen suitable for the use as a new advanced renewable bio-based metalworking fluid for manufacturing activities that corresponds to the energy saving benefits and environmental concerns.